Peningkatan Produksi Olahan Daun Kelor Organik melalui Teknologi Budidaya Kelor secara organik di Kecamatan Kinovaro Kabupaten Sigi Sulawesi Tengah: Increasing the Production of Organic Moringa Leaf Processes through Organic Moringa Cultivation Technology in Kinovaro District, Sigi Regency, Central Sulawesi - Yusran, Yusran; Korja, I Nengah; Wulandari, Retno; Rukmi, Rukmi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Moringa plants have high ethnobotanical value for the Kaili tribe in Porame village, Kinovaro district, Sigi Regency, Central Sulawesi. In this village, some MSMEs focus on producing organic moringa leaf products. However currently facing some problems, for example; the production of organic moringa leaves is still low both in terms of quality and quantity, and availability of raw materials for organic moringa leaves is still lacking due to the absence of moringa cultivation. Therefore, the empowerment program aims to find solutions to solve that problem. The approach method used in the form of education and training for partners by using counseling, training, and assistance methods in the form of technical guidance and community development in the production process of moringa leaves and their cultivation from seed to harvest, as well as the manufacture of organic fertilizers made from livestock manure. The results of the program that have been carried out are that there are organic moringa plantations covering an area of 0.5 Ha, products of organic moringa flour, etc, 20 sacks of organic fertilizers, and increasing in the knowledge and skills of farmer group members, especially in terms of organic moringa cultivation, post-harvest handling and diversification of its products.